2008
DOI: 10.1111/j.1741-4369.2008.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Txt msg n school literacy: does texting and knowledge of text abbreviations adversely affect children's literacy attainment?

Abstract: This paper reports on two studies which investigated the relationship between children's texting behaviour, their knowledge of text abbreviations and their school attainment in written language skills. In Study One, 11-12-year-old children provided information on their texting behaviour. They were also asked to translate a standard English sentence into a text message and vice versa. The children's standardised verbal and nonverbal reasoning scores were also obtained. Children who used their mobiles to send th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
5
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 12 publications
6
140
5
10
Order By: Relevance
“…Exceptions to this exist, as they do in class, but they are usually within the limits of the norm and with the expectation of teacher intervention if they do not. In contrast, communication in the sans-teacher groups is conducted in the youth's native "internet language" (Beverly, Wood, & Bell, 2008) and brings to the surface social conflicts and tensions in the peer group. It is also characterized by a sense of freedom, openness, lack of supervision, and sometimes even norm breaking.…”
Section: Teacher and Student Perspectives On Whatsapp Classroom Commumentioning
confidence: 99%
“…Exceptions to this exist, as they do in class, but they are usually within the limits of the norm and with the expectation of teacher intervention if they do not. In contrast, communication in the sans-teacher groups is conducted in the youth's native "internet language" (Beverly, Wood, & Bell, 2008) and brings to the surface social conflicts and tensions in the peer group. It is also characterized by a sense of freedom, openness, lack of supervision, and sometimes even norm breaking.…”
Section: Teacher and Student Perspectives On Whatsapp Classroom Commumentioning
confidence: 99%
“…These abbreviations can now also be found in poetry and spoken communication, and there are even prizes for the best SMS message (e.g., the Golden Thumb). Early use of SMS is related to children's literacy development, as studies have shown that the more text abbreviations preteenage children use in their text messages, the higher they score on tests for reading and vocabulary (Plester et al, 2008). Despite their popularity, very little is known about the processing of shortcuts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, little research has been done on the effects of the use of text speak on literacy. In the few studies that have been done (e.g., Plester, Wood, & Bell, 2008), researchers examined text speak and literacy in younger populations of students and found no links between text speak proficiency and lower standardized literacy scores. Thus, this study was designed to explore both the usage of the text speak vocabulary among American college students and the relationship between the use of text speak and literacy.…”
Section: Introductionmentioning
confidence: 99%